Seroprevalensi dan Isolasi Toxoplasma gondii pada Ayam Kampung di Bali (SEROPREVALENCE AND ISOLATION OF TOXOPLASMA GONDII AMONG FREE-RANGE CHICKENS IN BALI) - Dwinata, I Made; Oka, Ida Bagus Made; Suratma, Nyoman Adi; Damriyasa, I Made (Jurnal Veteriner, 2013)
The prevalence of Toxoplasma gondii in free range chickens is a good indicator of the prevalence of T.gondii oocysts in the environment and the meat of chicken is considered one of the sources of the humaninfection. A study to determine the seroprevalence of T.gondii in free ranging chickens in eight regency inBali have been undertaken. More over, attempt to isolate T gondii was also performed from the copropositivesample. Seroprevalence was detected using modified agglutination test (MAT) and isolation of T.gondiiwere performed from organs (heart and brain) using pepsin-HCl digestion method. Further the pathogenicityof the isolate was determined by bioassay using mice. The result showed that the seroprevalence was24.8% (31 out of 125 chickens examined). T.gondii was found in 17 of the 31 seropositive chickens (55%)more over all isolates were a vitulent to the mice.
Keywords: Toxoplasma gondii, Ayam kampung